Governance Mechanisms and Buyer Supplier Relationship: Static and Dynamic Panel Data Evidence from Tunisian Exporting SMEs - Meryem, Bellouma (International Journal of Economics and Financial Issues, 2011)
This study seeks to understand the effect of transactional and relational governance mechanisms on opportunism induced by the buyer supplier relationship. Using panel data of 386 Tunisian export companies between 2003 and 2008, the analysis shows that transactional as well as relational governance mechanisms are negatively related to the opportunistic behavior of the customer. In order to focus on internal corporate characteristics, the level of debt and the size of the buyer are controlled. This study supports the role of contracts as formal governance tool in reducing inter-firm opportunism which corroborates transaction cost economics. It also confirms some main notions in social exchange theory. The role of trust as relational mechanism in governing the buyer-supplier relationship has been verified. Finally, the findings of this paper sustain the complementarity view toward relational and transactional governance mechanisms. The paper offers insights to executives of companies to govern the buyer-supplier relationship in order to dispel opportunism by using simultaneously transactional and relational mechanisms. Keywords: Governance; Transactional governance mechanisms; Relational governance mechanisms; Opportunism, Buyer supplier relationship. JEL Classifications: G32; G34; L14